The Effect of Intravenous Glutamine Administration in Lowering AIF Expression in Renal Tubular Cells - Raihan Akbar Muhammad; Imam Susilo; Eko Budi Koendhori; Bambang Purwanto (Majalah Biomorfologi, 2025)
Highlights Glutamine, an amino acid, can help mitigate the side effects of cisplatin by boosting glutathione (GSH) levels, an antioxidant that counteracts oxidative stress. By reducing AIF protein expression and apoptosis, glutamine may protect kidney cells from cisplatin toxicity, potentially improving the safety of chemotherapy. Background: Cisplatin, a widely used chemotherapy that is effective for many forms of cancer, has nephrotoxic qualities that can reduce renal function. Due to its side effects, the usage of cisplatin is limited by its dose. Glutamine, an amino acid, possesses properties that can counteract the nephrotoxicity of cisplatin. Objective: This study aimed to analyze the effect of intravenous glutamine administration on the decrease of AIF expression and apoptosis in intraglomerular mesangial cells of cisplatin-exposed rats. Material and Method: Samples (n) consisting of 30 rats were divided into 3 groups, with each group containing 10 rats. Group P0 received no treatment, group P1 received an injection of cisplatin on the 7th day, and group P2 received glutamine on the 1st–7th day and an injection of cisplatin on the 7th day. After 72 h, the tissue samples were immunohistochemically processed and then observed under a light microscope with 400x magnification. AIF expression and apoptosis were measured in the Allred/H score. Result: AIF expression results were: P0 = 4,35(2,2-5,4); P1 = 5,9(4,8-6,3); P2 = 5,25(2,4-5,8). The AIF expression of P2 was found to be significantly lower (p = 0.008) than P1. Apoptosis results were: P0 = 5,2(4,7-5,5); P1 = 6,4(6,1-7,1); P2 = 5,7(4,8-5,9). The apoptosis level of P2 was found to be significantly lower (p = <0.0001) than P1. Strong correlations between the decrease in AIF expression and the apoptosis level were found (p = <0.0001). Conclusion: Glutamine contributes to the decreased AIF expression and apoptosis in intraglomerular mesangial cells of cisplatin-exposed rats.